The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1038/sj.ijo.0803220
|View full text |Cite
|
Sign up to set email alerts
|

Validity of body mass index and waist circumference in the classification of obesity as compared to percent body fat in Chinese middle-aged women

Abstract: Objective: To evaluate the validity of currently recommended obesity cutoffs of body mass index (BMI, in kg/m 2 ) and waist circumference (WC, in cm) for Asians by the WHO/IASO/IOTF and for Chinese by the Working Group on Obesity in China (WGOC) using the percentage body fat (%BF)-obesity criteria. Design: A cross-sectional study. Subjects: A total of 1122 community-based Hong Kong Chinese women aged between 41 and 63 years. Measurements: Total %BF and percent truncal fat (%TF) were measured using dual-energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 28 publications
1
44
0
1
Order By: Relevance
“…Stavropoulous-Kalinoglou previously suggested that the BMI cut-point for obesity be reduced by 2 kg/m 2 (i.e., to 28) for individuals with RA; our analyses support cut-points that are even lower. Other investigators have also noted in non-RA populations that the current obesity cut-point of BMI≥30 is too high, has low sensitivity to detect adiposity in the general population, and is not appropriate for specific ethnic groups, and have identified alternate BMI obesity cut-points very similar to those we identified, ranging from 25-25.8(40-45). …”
Section: Discussionsupporting
confidence: 63%
“…Stavropoulous-Kalinoglou previously suggested that the BMI cut-point for obesity be reduced by 2 kg/m 2 (i.e., to 28) for individuals with RA; our analyses support cut-points that are even lower. Other investigators have also noted in non-RA populations that the current obesity cut-point of BMI≥30 is too high, has low sensitivity to detect adiposity in the general population, and is not appropriate for specific ethnic groups, and have identified alternate BMI obesity cut-points very similar to those we identified, ranging from 25-25.8(40-45). …”
Section: Discussionsupporting
confidence: 63%
“…Therefore, metabolic syndrome was defined based on the modified criteria of the ATP III, in which BMI (≥ 25 kg/m 2 ) was substituted for the waist circumference measurement. Both waist circumference and BMI are accurate predictors of total body fat, however, in the Asian population (40). Furthermore, the present study suggests that the modified ATP III criteria are useful for detecting the risk for developing CKD.…”
Section: Discussionmentioning
confidence: 84%
“…2 The cutoff points of 24 for overweight and 28 for obesity are the BMI standards for the Asian population as a whole. Their empirical validity is under discussion and a domain of research; a recent study conducted among 1122 middle-aged (41-63 years old) Chinese women suggests that the recommended BMI cutoffs are appropriate (Chen et al, 2006). 3 The CNNHS classify the survey areas in six different categories according to criteria of economic development levels and geographic typology: large cities (such as Beijing or Shanghai), medium and small cities (such as small provincial capitals), first class rural areas (such as Yangtze delta), second class rural areas (such as Northeast plain or Sichuan basin), third class rural areas and fourth class rural areas (e.g.…”
Section: Searching For Consumer Segmentsmentioning
confidence: 98%